Unexpected Anal Squamous Cells Carcinoma after Open Hemorrhoidectomy - Navarra Luca; Abruzzese Valentina; Sista Federico; Pietroletti Renato (Case Reports in Surgery)
We report a case of unexpected anal squamous cells carcinoma found in hemorrhoidectomy specimen. The patient had a 3-year history of prolapsing hemorrhoids. A prolapsing hemorrhoid was present at eleven o’clock in lithotomy. Milligan-Morgan was performed and gross examination of the specimen was unremarkable. Histopathologic evaluation showed noninvasive squamous cells carcinoma. The present case report evidences the opportunity of routine histopathologic analysis of hemorrhoidal specimens particularly in case of long-standing prolapse. Questions arise in the option of those techniques where no specimens are collected or tissue is excised far from deceased area.